2020
DOI: 10.3390/ijerph17041440
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acute Kidney Injury in the Perioperative Period on the Incidence of Postoperative Delirium in Patients Undergoing Coronary Artery Bypass Grafting—Observational Cohort Study

Abstract: Recent data indicate that acute kidney damage leads to inflammation in the brain and other distant organs. The purpose of this study was to investigate the effect of acute kidney injury (AKI) according to the Kidney Disease Improving Global Outcome (KDIGO) criteria on the occurrence of postoperative delirium in patients undergoing coronary artery bypass grafting (CABG). We performed a retrospective cohort analysis that included all consecutive patients undergoing elective CABG. The CAM-ICU (Confusion Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…At present, the risk factors for POD is thought to be multifactorial. Referring to previous literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , we found that following factors are independent high-risk factors for the development of POD: type of surgical procedures, major emergency surgery, age, ASA grade, pain, postoperative intensive care admission, prolonged uid fasting, anemia, general anesthesia, benzodiazepines, depression/anxiety, and medical comorbidity, education and preoperative functional status.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…At present, the risk factors for POD is thought to be multifactorial. Referring to previous literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , we found that following factors are independent high-risk factors for the development of POD: type of surgical procedures, major emergency surgery, age, ASA grade, pain, postoperative intensive care admission, prolonged uid fasting, anemia, general anesthesia, benzodiazepines, depression/anxiety, and medical comorbidity, education and preoperative functional status.…”
Section: Discussionsupporting
confidence: 68%
“…The symptoms of delirium can occur suddenly or slowly over a period of hours or days, and may be so slight that they go unnoticed or so serious that they could be life threatening. Although the etiology is not well understood, multiple risk factors for POD were described in previous studies, including: age [4], female sex [5,6], longer duration of surgery [6], choice of general anesthetics [7], imbalance of electrolyte [8], and use of intraoperative or postoperative drugs [9] (benzodiazepines or ketamine) and hypothermia [10], being operated on and kept in ICUs [11], infections [12], nutritional status identi ed by albumin level [13], pain [14], comorbidities [15][16][17][18] (such as hypothyroidism, renal dysfunction, diabetes, obesity, valvar disease, hypertension, congestive heart failure), withdrawal of alcohol [19], and psychosocial environment [20] (depression/anxiety or psychoses), and even subclinical cerebral damage [21], inability to ambulation [22], treatment with multiple drugs [13]. Preclinical and clinical research in recent years has uncovered more about the pathophysiology of POD and maybe yield some therapeutic options or effective perioperative intervention in order to reduce the prevalence of POD, but up to date, POD is still a common complication after major surgery in older patients and is becoming a great concern because of high incidence and a lengthy hospitalization period.…”
Section: Introductionmentioning
confidence: 99%
“…Whether changes in creatinine after POD1 affect delirium is still unclear. However, data from cardiac surgery suggests that acute kidney injury in the 2 days postoperatively increases the risk of delirium 19 …”
Section: Discussionmentioning
confidence: 99%
“…This retrospective study characterized the large-sample outcomes of patients undergoing IMV secondary to acute exacerbation of COPD and provided compelling evidence that increasing age, male sex, alcoholism with active abstinence, current smoking, stage 3 AKI, 19,20 and an ASA physical status of III tend to be noteworthy risk factors for the development of ICUD.…”
Section: Discussionmentioning
confidence: 99%